2015
DOI: 10.1371/journal.pone.0135774
|View full text |Cite
|
Sign up to set email alerts
|

Passive Immunization in JNPL3 Transgenic Mice Using an Array of Phospho-Tau Specific Antibodies

Abstract: Recent work from our lab and few others have strongly suggested that immunotherapy could be an effective means of preventing the development of tau accumulation in JNPL3 transgenic mice, carrying the human P301L mutation. The aim of this study was to test the efficacy of a variety of specific tau monoclonal antibodies in JNPL3. Starting at 3 months of age, mice were treated for 4 months with weekly intraperitoneal injections of saline or purified tau monoclonal antibodies (10mg/Kg) different in specificity for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 31 publications
0
28
0
Order By: Relevance
“…4 In one tau-transgenic mouse model, the phospho-tau antibodies specific to distinct phosphorylation sites affected tau pathology differently, with a certain phospho-tau antibody (PG5, pS409) even worsening the pathology. 13 It will be important to screen multiple phosphorylation sites in the same in vitro and/or in vivo assay to identify the most efficient therapeutic antibody.…”
Section: Discussionmentioning
confidence: 99%
“…4 In one tau-transgenic mouse model, the phospho-tau antibodies specific to distinct phosphorylation sites affected tau pathology differently, with a certain phospho-tau antibody (PG5, pS409) even worsening the pathology. 13 It will be important to screen multiple phosphorylation sites in the same in vitro and/or in vivo assay to identify the most efficient therapeutic antibody.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the importance of antibody charge for intracellular access has been well studied for potential cancer antibody therapies but not for tau antibodies or similar approaches targeting other amyloids. We have recently shown that antibody charge can robustly affect antibody uptake into neurons [19,64], which may explain why some labs detect tau antibodies inside neurons [2,79,11,12,14,39,40,65], whereas others do not for different antibodies [34,41,43]. This issue has particular importance for clinical trials because the humanized antibodies are likely to have a different charge than the mouse antibodies that they are based on.…”
Section: How Does It Work?mentioning
confidence: 99%
“…Targeting numerous other epitopes has been shown to be effective in several studies. These include non-phosphorylated- [27,30,32,41,42,4648,69,70], phosphorylated- [20,24,25,27,29,35,39,43,49], conformational-/oligomeric [20,31,33,34,40,44,45], and a truncated epitope [66,71]. Since these studies have various designs, they cannot be easily compared to identify the best epitopes to target.…”
Section: How Does It Work?mentioning
confidence: 99%
“…So far, most of known abnormally phosphorylated states are detectable only at very late stages of hyperphosphorylation which seems that clearance is too late to retrieve neuronal function. 25,51 While there have been extensive attempts to neutralize tau toxicity employing mAbs removing different p-tau epitopes, only by targeting specific epitopes like pSer202, pSer413, pThr231 and pSer422 a decrease in insoluble/soluble tau in the brain was observable and the brain loss of function has been stopped in those mice models. 52 Furthermore, treatment with a phospho-tau peptide (containing the phosphorylated PHF-1 epitopes Ser 396 and Ser 404) in animal models prior to the onset of pathology has proven successful in preventing development of tau aggregates in the Tg P301L mouse tau model.…”
Section: Tau Immunotherapy Has Been Promisingmentioning
confidence: 99%